THE SUFI LEGACY OF AZIZIDDIN NASAFI AND ITS STUDY - Narzieyev Zubaydillo Ibodilloyevich Ibodilloyevich (Journal of Learning on History and Social Sciences, 2024)
The following article insights on the the sufi legacy of Aziziddin Nasafi and its study based on his treaties “Kashf-ul haqayiq” and Kitab al-insan ul kamil”. The alternative version is also commented.